2013
DOI: 10.2139/ssrn.2386700
|View full text |Cite
|
Sign up to set email alerts
|

Politics, Political Settlements and Social Change in Post-Colonial Rwanda

Abstract: This document is an output from a project funded by the UK Aid from the UK Department for International Development (DFID) for the benefit of developing countries. However, the views expressed and information contained in it are not necessarily those of or endorsed by DFID, which can accept no responsibility for such views or information or for any reliance placed on them.We cannot turn the clock back nor can we undo the harm caused, but we have the power to determine the future and to ensure that what happene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Such insecurity forces ruling elites to commit to delivering economic development. This is in agreement with many scholars, including Golooba-Mutebi (2008), who argue that ruling Rwanda Patriotic Front (RPF) elites perceive their leadership to be legitimised by achieving economic development. Such vulnerability was central to the experience of many developmental states (Castells 1992; Putzel 2002; Doner et al 2005).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Such insecurity forces ruling elites to commit to delivering economic development. This is in agreement with many scholars, including Golooba-Mutebi (2008), who argue that ruling Rwanda Patriotic Front (RPF) elites perceive their leadership to be legitimised by achieving economic development. Such vulnerability was central to the experience of many developmental states (Castells 1992; Putzel 2002; Doner et al 2005).…”
Section: Introductionsupporting
confidence: 88%
“…Rwanda scholars have also failed to take into account the possibility that a mixture of inclusive and exclusionary political dynamics take place during development transitions. Scholars who are positive about the RPF government have argued that the current government is ‘more inclusive than at any other time after independence’ (Golooba-Mutebi 2008: 29). The Rwandan Alliance for National Unity (RANU) was created as an ‘inclusive’ political party.…”
Section: ‘Consensus’ and ‘Inclusiveness’ In Political Settlementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the genocide, and primarily after 2000, the RPF has been widely cited (Golooba-Mutebi, 2013;Goodfellow, 2014;Behuria, 2016;Behuria and Goodfellow, 2016;Williams, 2017;Chemouni, 2018) as an example of a 'potential developmental coalition' or 'strong developmental regime' in line with existing political settlements frameworks (Khan, 2010;Whitfield et al, 2015). Characterising Rwanda in this way suggests that factions excluded from the ruling coalition are relatively weak, as are lower-level factions within the ruling coalition itself.…”
Section: Rwanda's Political Settlement and The Banking Sectormentioning
confidence: 99%
“…This study showed that the government's motivation for introducing the VUP was what the government perceived to be a distributional crisis after evaluations of the national development strategy in 2007 showed high growth rates, rising income, and inter-regional inequality, as well as stagnating rates of poverty reduction. Since coming to power following the genocide against the Tutsis in 1994, the Rwandan Patriotic Front (RPF) has legitimized its rule by marking a clean break from the regional and ethnic divisions of the past, instead promoting a narrative of national unity, seeking to provide all Rwandan citizens with a stake in the country's future and taking care to maintain impartiality in policy implementation development (Golooba-Mutebi 2013;Williams 2017). Rising inequality and the struggle to reduce poverty threatened this narrative, leading to strong political pressure to come up with an ambitious programme that would quickly address these problems.…”
Section: Introductionmentioning
confidence: 99%